Development of methodology of experimental studies of control in crystallization of castings by optimizing the thermophysical properties of the elements of the gating system - Yu. N. Fasevich; F. I. Rudnitsky (Литьë и металлургия)
The fundamental purpose of the proposed research is to identify and analyze important technological parameters by obtaining the characteristics of the studied thermal properties of hot tops, providing a stable mode of applying hydrodynamic pressure before the crystallization of the casting due to the heating of hot top part of the interrelated elements of the «gating system–casting» on the basis of means of providing computational experiments from the point of view of managing the production process of blanks of wearing parts.